EFFECTIVENESS OF FACIAL ACCUPRESURE THERAPY IN THE REDUCTION OF ANXIETY IN POSTPARTUM WOMEN - Zulfiana, Evi; Umriaty, Umriaty (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
The puerperium is the period of the return of the reproductive organs in their pre-pregnancy state. In most postpartum mothers experience anxiety, this condition if not immediately overcome the risk of postpartum mothers experiencing baby blues to lead to postpartum maternal depression. This study aims to determine the effectiveness of complementary obstetric services on facial acupressure to reduce anxiety levels in postpartum mothers. This research method is quantitative with quasy experimental design with a two-group pre-test design – post test control group design. The treatment group was postpartum mothers who were given facial acupressure every 10-15 minutes for 3 days and the control group were postpartum mothers who were not given facial acupressure, The population in this study was 40 postpartum mothers, The samples used were postpartum mothers day 3-10 days, sampling by purposive sampling, 20 postpartum mothers in the treatment group and 20 in the control group. Bivariate anailisa used Wilcoxon's alternative test with research criteria for postpartum mothers 3-10 days, postpartum mothers for the first time and mothers who were willing to be respondents. The results of statistical tests using Wilcoxon obtained by the treated group with a P-value of 0.000 (P0.05) showed that the hypothesis was accepted so that facial acupressure was effective in reducing anxiety levels in postpartum mothers.